2007
DOI: 10.1002/jcb.21209
|View full text |Cite
|
Sign up to set email alerts
|

Stromal biology of pancreatic cancer

Abstract: The genetic paradigm of cancer, focused largely on sequential molecular aberrations and associated biological impact in the neoplastic cell compartment of malignant tumors, has dominated our view of cancer pathogenesis. For the most part, this conceptualization has overlooked the dynamic and complex contributions of the surrounding microenvironment comprised of non-tumor cells (stroma) that may resist, react to, and/or foster tumor development. Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
234
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(244 citation statements)
references
References 140 publications
(156 reference statements)
2
234
0
8
Order By: Relevance
“…PDAC tumor stroma serves as a mechanical barrier and promotes tumor forma-tion, progression, invasion, and metastasis development. [32][33][34] Treatment with nab-paclitaxel alone or nab-paclitaxel in combination with gemcitabine has been shown to decrease cancer-associated fibroblast (CAF) content, inducing a marked alteration in cancer stroma that result in tumor softening both preclinically 29 and clinically 28 . In our studies, we also found that the G C nP doublet significantly reduced the number of a-SMA positive fibroblasts as well as reduced extracellular collagen.…”
Section: Discussionmentioning
confidence: 99%
“…PDAC tumor stroma serves as a mechanical barrier and promotes tumor forma-tion, progression, invasion, and metastasis development. [32][33][34] Treatment with nab-paclitaxel alone or nab-paclitaxel in combination with gemcitabine has been shown to decrease cancer-associated fibroblast (CAF) content, inducing a marked alteration in cancer stroma that result in tumor softening both preclinically 29 and clinically 28 . In our studies, we also found that the G C nP doublet significantly reduced the number of a-SMA positive fibroblasts as well as reduced extracellular collagen.…”
Section: Discussionmentioning
confidence: 99%
“…The often prominent desmoplastic stroma in pancreatic ductal adenocarcinomas includes activation of fibroblasts and myofibroblasts transformation, inflammation, neovasculation and enhanced secretion of cytokines, matrix proteins and metalloproteinases. 30 This stroma plays a role in tumor proliferation, progression, angiogenesis, cell death and matrix remodeling. The observed microRNA expression profiles in each cancer sample may depend on the distribution of tumor cells and stromal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,23,24 MicroRNAs are stable in formalin-fixed paraffin-embedded samples. 28,29 Tumor cells in pancreatic ductal adenocarcinomas are often located in small groups surrounded by an abundant stromal tissue 30 and information related to microRNAs from the stromal tissue may be lost if micro-dissection is applied.…”
mentioning
confidence: 99%
“…Thus, tissuespecific interactions between tumour cells and the stromal and vascular compartments, which are increasingly recognised as major determinants of the tumour phenotype, were maintained (Blouw et al, 2003;Chu et al, 2007). Second, orthotopic pancreatic tumours metastasised using the clinically relevant route of lymphatic metastasis and thereby offered information that is unavailable from subcutaneous xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of diagnosis, most patients with pancreatic cancer require systemic therapy as invasive growth and metastatic spread occur early in the course of the disease Chu et al, 2007). Unfortunately, pancreatic cancer has proven remarkably resistant to current systemic treatment modalities including chemo-and radiotherapies (Xiong et al, 2006), suggesting a unique combination of molecular alterations accounts for this highly unfavourable biological profile.…”
mentioning
confidence: 99%